El Carmen de Bolívar: a lesson not to be forgotten - Carlos Fernando Grillo-Ardila (Federación Colombiana de Obstetricia y Ginecología, 2014)
The growing concern regarding the safety of vaccination against human papillomavirus (HPV) is no secret to anyone in Colombia. This concern arises from recent events in El Carmen de Bolívar a town located close to the north coast in the country, where more than 500 girls who were vaccinated presented a variety of symptoms that required medical care in the local hospital. The event reached such a magnitude that it not only overwhelmed the local health services in the township but also required the joint effort of several agencies of the national, department and regional levels to placate the irate population, restore law and order, and shed light on the facts (1). Multiple theories have been proposed in an attempt to explain the sequence of events, but two of them in particular have been the focus of our attention: the symptoms reported may be explained as an adverse reaction to the vaccine, or as a somatoform disorder (mass psychogenic response). The objective of this editorial is to contribute to the current discussion by means of a critical assessment of the evidence regarding the safety of HPV vaccination and to approach the complexity of the problem that took place at El Carmen de Bolivar as a form of reflection on the issue.